Work and labor in the digital age - P. Vallas, Steven; Kovalainen, Anne (Bingley, U.K. : Emerald Publishing Limited, 2019)
This volume presents the most recent studies of work and labor in the digital age as it unfolds in both Europe and the United States.One of the critical questions facing modernity concerns the reconfiguration of paid employment, which has been subject to wholesale changes that have widespread consequences for workers, their families, and the institutional structure that characterizes capitalist societies. A key driver of these changes has been the digital revolution and the rapid proliferation of the gig economy. Together with social network sites for hiring, the spread of robotics, and the rise of artificial intelligence and machine learning, they leave virtually no occupation untouched.
Prelims -- Introduction: Taking stock of the digital revolution -- Chapter 1: Work and value creation in the platform economy -- Chapter 2: Technology-driven task replacement and the future of employment -- Chapter 3: Platforms at work: automated hiring platforms and other new intermediaries in the organization of work -- Chapter 4: Black holes and purple squirrels: a tale of two online labor markets -- Chapter 5: Brave new digital work? New forms of performance control in crowdwork -- Chapter 6: Labor market inclusion through predatory capitalism? The "sharing economy," diversity, and the crisis of social reproduction in the Belgian coordinated market economy -- Chapter 7: Work-games in the gig-economy: a case study of uber drivers in the city of monterrey, Mexico -- Index.
Includes index.
Print version record.
Keywords: Labor -- Europe; Labor -- United States; Work -- Social aspects -- Europe; Work -- Social aspects -- United States; Organizational effectiveness -- Technological innovations; Labor supply -- Effect of technological innovations on; Internet -- Social aspects; Social Science -- Anthropology -- Cultural & Social; Sociology: work & labour